A study to assess prevalence of obesity among medical students of G.R. medical college, Gwalior, M. P., India - Tiwari, Ranjana; Jain, Vikas; Rajput, Ajit Singh; Bhagwat, A. K.; Goyal, Manish; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is emerging as a serious problem throughout the world, not only among adults but also children, teenagers and young adults. Medical education is stressful throughout the whole course of training. Overweight and obesity is one of the preventable cause of morbidity and mortality. The social implications of obesity are a major problem that is often neglected. Objectives of current study were to assess the prevalence of overweight and obesity in medical students and to assess the factors influencing the development of overweight and obesity. Methods:The present study was a cross sectional study of IInd semester medical students in which, a total of 131 students were included. The study involved administration of a pretested questionnaire to the students and their anthropometric measurements. Results:In a batch of 150 students 131 participated in the study in which 90 (68.70%) were males and 41 (31.30%) were females. The prevalence of overweight was 13 (9.93%) and the prevalence of obesity was 2 (1.53%). Conclusion:The study showed a high prevalence of overweight and obesity among the medical students. At the time of anthropometric measurements awareness was created for their weight and for the promotion of physical activity among medical students.